2003
DOI: 10.1002/mds.10518
|View full text |Cite
|
Sign up to set email alerts
|

Two‐year follow‐up of subthalamic deep brain stimulation in Parkinson's disease

Abstract: We studied 48 patients after bilateral subthalamic nucleus deep brain stimulation (STN‐DBS) who were evaluated 6 months after the surgical procedure using the Unified Parkinson's Disease Rating Scale (UPDRS) in a standardized levodopa test. Additional follow‐up was available in 32 patients after 12 months and in 20 patients after 24 months. At 6 months follow‐up, STN‐DBS reduced the UPDRS motor score by 50.9% compared to baseline. This improvement remained constant at 12 months with 57.5% and at 24 months with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
187
0
10

Year Published

2006
2006
2016
2016

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 269 publications
(207 citation statements)
references
References 21 publications
10
187
0
10
Order By: Relevance
“…There were 4 Class III studies [36][37][38][39] and 10 Class IV studies. [40][41][42][43][44][45][46][47][48][49] All studies examined bilateral DBS of the STN. Only the Class III studies are discussed in detail.…”
Section: Surgical Therapy Question 4: For Patients With Pd Does Dbsmentioning
confidence: 99%
See 1 more Smart Citation
“…There were 4 Class III studies [36][37][38][39] and 10 Class IV studies. [40][41][42][43][44][45][46][47][48][49] All studies examined bilateral DBS of the STN. Only the Class III studies are discussed in detail.…”
Section: Surgical Therapy Question 4: For Patients With Pd Does Dbsmentioning
confidence: 99%
“…[36][37][38][39][40][41]43,44,[46][47][48][49] Only the Class II studies are discussed in detail. Although these studies were rated Class IV relative to Question 4 regarding efficacy, they earned grades of Class II relative to prognosis for Question 5.…”
Section: Question 5: Which Factors Predict Improvement After Dbs?mentioning
confidence: 99%
“…The calculated incidence of complications associated with laparoscopic bariatric surgery, obtained from the case series, 4,8,10,17,28,38,44,45,52,74,77,82,83,91,120 is summarized in Table 1; complications associated with DBS studies are shown in Table 2. 6,7,9,12,16,20,26,27,31,37,39,47,[55][56][57][58][59][60][61]64,[67][68][69]71,78,80,81,84,[86][87][88][89][96][97]…”
Section: Resultsmentioning
confidence: 99%
“…205 It is important to recognize that these effects were observed in patients with Parkinson's disease treated with DBS. It is not yet clear what side effects may occur in non-Parkinsonian patients that undergo DBS surgery and long-term treatment-likely the potential for side effects will depend greatly on the precise stimulation site.…”
Section: Deep Brain Stimulationmentioning
confidence: 99%